Developing health policies in patients presenting with SARS-CoV-2: consider tuberculosis (2020)
The global pandemic of COVID-19 has led to a prominent public health response, with many countries introducing highly proactive measures for screening and identifying severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). COVID-19 has gained the dubious honour as the single greatest infectious cause of global mortality in 2020. Active COVID-19 disease encompasses cough, fever, fatigue, and shortness of breath among other signs and symptoms.1,2 Risk factors for severe COVID-19 disease include diabetes, chronic obstructive pulmonary disease, immune suppression, and age. Some select population demographics (people who are Black, Hispanic, or a member of another ethnic minority group), in association with overcrowded housing and homelessness, are also at risk of severe disease and mortality